2018
DOI: 10.1002/art.40430
|View full text |Cite
|
Sign up to set email alerts
|

Increased Circulating Follicular Treg Cells Are Associated With Lower Levels of Autoantibodies in Patients With Rheumatoid Arthritis in Stable Remission

Abstract: Circulating Tfr cells are increased as patients with RA achieve stable remission of disease, and increased Tfr cells can suppress autoimmunity in RA patients to stabilize their condition. Our results provide novel insight into RA pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
103
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(114 citation statements)
references
References 30 publications
6
103
1
Order By: Relevance
“…Interestingly due to their CD25 int nature CD45RA − cTfr find themselves in the fraction (FRIII) of blood Tregs that we previously identified as primarily Foxp3 int CD25 int non-Tregs (70). However, since we and others have confirmed that cTfr retain stable expression of Foxp3, a Treg-type demethylation signature, and suppressive function, it seems that FRIII may contain a mixture of Tregs and non-Tregs (26, 68, 71). This mixed nature of FRIII was recently confirmed by the finding that CD127 − CD25 int CD45RA − FRIII Tregs can be further divided into CD49d + CCR4 − , CCR4 − CD49d − , and CCR4 + CD49d − cells, with the CD49d fraction expressing inflammatory cytokines (72).…”
Section: Circulating Tfrmentioning
confidence: 70%
See 2 more Smart Citations
“…Interestingly due to their CD25 int nature CD45RA − cTfr find themselves in the fraction (FRIII) of blood Tregs that we previously identified as primarily Foxp3 int CD25 int non-Tregs (70). However, since we and others have confirmed that cTfr retain stable expression of Foxp3, a Treg-type demethylation signature, and suppressive function, it seems that FRIII may contain a mixture of Tregs and non-Tregs (26, 68, 71). This mixed nature of FRIII was recently confirmed by the finding that CD127 − CD25 int CD45RA − FRIII Tregs can be further divided into CD49d + CCR4 − , CCR4 − CD49d − , and CCR4 + CD49d − cells, with the CD49d fraction expressing inflammatory cytokines (72).…”
Section: Circulating Tfrmentioning
confidence: 70%
“…One group found that these cells were unable to suppress antibody production (68) while several groups found the opposite (26, 35, 71). Interestingly, Liu et al, found that cTfr suppressive activity increased in correlation with the sequential shift of cTfr from FRIII Foxp3 int into a highly-activated Foxp3 hi phenotype from healthy donors > active RA patients > patients in remission.…”
Section: Circulating Tfrmentioning
confidence: 99%
See 1 more Smart Citation
“…Altered frequencies and/or the suppressive capacity of cTfr cells have been elucidated in a multitude of AIDs, including systemic AIDs and organ‐specific AIDs (shown in Table ). Systemic AIDs involve rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), Sjögren's syndrome (SS), ankylosing spondylitis (AS), IgG4‐related disease (IgG4‐RD) and common variable immune deficiency (CVID) . Organ‐specific AIDs involve multiple sclerosis (MS), myasthenia gravis (MG), Hashimoto's thyroiditis (HT), primary biliary cholangitis (PBC), type 1 diabetes (T1D) and ulcerative colitis (UC) .…”
Section: Tfr Cells In Human Diseases and Animal Modelsmentioning
confidence: 99%
“…The frequency of cTfr cells has negative or no correlation with disease activity, and the ratio of cTfr/cTfh is correlated with disease activity . Moreover, increased cTfr cells with enhanced suppressive function and activated CD45RA − Foxp3 high cTfr subset have been found in patients with RA in stable remission compared with patients with active RA and healthy controls . Percentages of cTfr and cTfh cells are decreased when prescribed with methotrexate …”
Section: Tfr Cells In Human Diseases and Animal Modelsmentioning
confidence: 99%